Implementasi Pendidikan Karakter Pluralis melalui Kearifan Local Budaya Trisilas Local Wisdom Scale di SD - Nugraha, Jaka (Universitas Nahdlatul Ulama Pasuruan, 2022)
The integration of local wisdom with the trisylas culture of the local wisdom scale is one form of interesting learning innovation in inculcating the pluralist character of elementary school students. This study aims to describe the implementation of localwisdom of the trisylas local wisdom scale in the pluralist character education of students in elementary schools. This study uses descriptive qualitative methods to explore phenomena that appear naturally. The subjects of this study were elementary schoolstudents at SDN Cicalengka X, Bandung Regency. The findings stated that the values contained in the local wisdom of the trisylas culture of the local wisdom scale greatly influenced the formation of the pluralist character of students in Cicalengka X Elementary School, Bandung Regency. In particular, it is concluded that with the implementation of local wisdom, the Trisilas local wisdom scale, students form the character of mutual tolerance, love each other, respect each other, and work together.